2007
DOI: 10.1111/j.1365-2583.2006.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite flanking region similarities among different loci within insect species

Abstract: Although microsatellites are ubiquitous in eukaryota, the number of available markers varies strongly among taxa. This meta-analysis was conducted on 32 insect species. Sequences were obtained from two assembled whole genomes, whole genome shotgun (WGS) sequences from 10 species and screening partial genomic libraries for microsatellites from 23 species. We have demonstrated: (1) strong differences in the abundance of microsatellites among species; (2) that microsatellites within species are often grouped into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 76 publications
(74 reference statements)
7
77
1
Order By: Relevance
“…Such SSR association with a retrotransposon is in agreement with the data of Temnykh et al (2001) and Inukai (2004) on rice, of Koike et al, (2006) on wheat and barley (Ramsay et al, 1999;Vicient et al, 2005) as well as animals (Wilder and Hollocher, 2001;Meglecz et al, 2007;Van't Hof et al, 2007). In particular, the study of Ramsay et al (1999) showed an intimate association of SSRs with retrotransposons in barley.…”
Section: Retrotransposons As Microsatellite Dispersal Agentssupporting
confidence: 89%
See 1 more Smart Citation
“…Such SSR association with a retrotransposon is in agreement with the data of Temnykh et al (2001) and Inukai (2004) on rice, of Koike et al, (2006) on wheat and barley (Ramsay et al, 1999;Vicient et al, 2005) as well as animals (Wilder and Hollocher, 2001;Meglecz et al, 2007;Van't Hof et al, 2007). In particular, the study of Ramsay et al (1999) showed an intimate association of SSRs with retrotransposons in barley.…”
Section: Retrotransposons As Microsatellite Dispersal Agentssupporting
confidence: 89%
“…These findings are reflected in the relatively high frequency of SSR transferability among legume species (Pandian et al, 2000;Gutierrez et al, 2005). The contradictory view that microsatellites are derived from repetitive (high copy number) sequences is supported by several reports in plants (Ramsay et al, 1999;Temnykh et al, 2001;Koike et al, 2006;Tero et al, 2006), insects (Wilder and Hollocher, 2001;Meglecz et al, 2007;Van't Hof et al, 2007) and nematodes (Johnson et al, 2006), suggesting a link between transposable elements and microsatellite sequence. One theory is that the transposable element harboring the proto-microsatellite sequence distributes it genome-wide by transposition and this sequence subsequently develops into a full microsatellite.…”
Section: Introductionmentioning
confidence: 94%
“…Second, the occurrence of cryptic repetitive DNA in microsatellite flanking regions overlapping with PCR binding sites can result in the amplification of products of unexpected sizes or in the difficulty in amplification of products representing a single locus (Zhang, 2004). Cryptic repetitive DNA and high similarity among microsatellite flanking regions, which are very commonly found in plants (Tero et al, 2006), have also been recently identified from a number of insects and crustaceans (Meglécz et al, 2004(Meglécz et al, , 2007Van't Hof et al, 2007;Bailie et al, 2010). These are thought to be primarily generated during DNA multiplication or duplication processes (Meglécz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties are encountered because alleles that originate from independently segregating loci typically are scored, and render genetic markers unsuitable for population or linkage analysis (Anthony et al 2001;Fauvelot et al 2006;Anderson et al 2007). Microsatellite families are known among insect species (Meglécz et al 2007), but appear pronounced within lepidopteran species due to a yet undescribed common ancestry that is shared among genomes.…”
Section: Introductionmentioning
confidence: 99%